2021
DOI: 10.1200/go.20.00147
|View full text |Cite
|
Sign up to set email alerts
|

Screen, Notify, See, and Treat: Initial Results of Cervical Cancer Screening and Treatment in Rwanda

Abstract: PURPOSE To describe the first year results of Rwanda's Screen, Notify, See, and Treat cervical cancer screening program, including challenges encountered and revisions made to improve service delivery. METHODS Through public radio broadcasts, meetings of local leaders, church networks, and local women's groups, public awareness of cervical cancer screening opportunities was increased and community health workers were enlisted to recruit and inform eligible women of the locations and dates on which services wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…The sample size of females aged 25-49 years ranged from 5882 in Ethiopia to 9186 in Tanzania. The median age and interquartile ranges were 32 years (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) in Ethiopia, 33 years (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in Zambia and 34 years (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in Malawi, Rwanda, and Tanzania. The rate of self-reported cervical pre-cancer screening was lowest in Rwanda (3.5% [95% CI 3.1%-4.0%]) and highest in Zambia (17.1% [95% CI 15.8%-18.5%]) and Zimbabwe (17.4% [95% CI 16.1%-18.8%]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size of females aged 25-49 years ranged from 5882 in Ethiopia to 9186 in Tanzania. The median age and interquartile ranges were 32 years (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) in Ethiopia, 33 years (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in Zambia and 34 years (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in Malawi, Rwanda, and Tanzania. The rate of self-reported cervical pre-cancer screening was lowest in Rwanda (3.5% [95% CI 3.1%-4.0%]) and highest in Zambia (17.1% [95% CI 15.8%-18.5%]) and Zimbabwe (17.4% [95% CI 16.1%-18.8%]).…”
Section: Resultsmentioning
confidence: 99%
“…Governments could build cervical pre-cancer screening around a target population, such as eligible schoolgirls and colleague students, which would assist in addressing socioeconomic inequalities. For example, Rwanda vaccinated more than 90% of schoolgirls against HPV from 2011 to 2012, through designated "health days" which were adapted for other sexual reproductive and maternal health purposes [37,38]. This approach reduced time, money, and other costs of accessing HPV vaccination for girls, and other maternal health services for women [37].…”
Section: Discussionmentioning
confidence: 99%
“…[20] Cervical cancer screening helps its early detection and early treatment for those diagnosed with cervical cancer which results in favorable outcomes and survival. [5,21] When pre-cancerous lesions are detected, they can be treated with available cost-effective technologies such as cryotherapy or Loop Electrosurgical Excision Procedure (LEEP) which can decrease cervical cancer occurrence and its-related mortality in LMIC. [22] Rwanda has integrated non-communicable diseases prevention and control programs in primary health care services in the purpose to improve NCD care including screening and treatment services.…”
Section: Discussionmentioning
confidence: 99%
“…[4] An estimated 311,000 women died from cervical cancer worldwide in 2018, and 85% of these deaths occurred in low-and-middle income countries (LMIC) with Sub-Sahara Africa being the most affected. [4,5] High cancer-related mortality rate in LMIC is attributed to the inadequate access to effective screening services which results in low awareness of the diseases during its early stages and late diagnosis at the advanced stages with poor treatment outcomes. [6][7][8][9] Cervical cancer is preventable and curable if detected early enough and treated with available cost-effective technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Cytology as a screening method is difficult to implement in developing countries due to a limitation in the number of cytologists. We and other research groups have shown that HPV screening may be used to identify women with high-grade cervical lesions in Rwanda [ 5 , 6 ]. While different approaches may be undertaken to reduce the number of cervical cancer cases, there is a risk of over-treatment, and the follow-up of patients at risk of cervical cancer is difficult to organize in many sub-Saharan countries.…”
Section: Introductionmentioning
confidence: 99%